The role of β-endorphins and catechol estrogens on the hypothalamic-pituitary axis in female athletes - Russell, Jeffrey B.; Mitchell, Dorothy E.; Musey, Paul I.; Collins, Delwood C. (Fertility and sterility, 1984)
Competitive swimmers were followed over a 2-year period when they trained at different levels of exercise which coincided with distinct changes in their menstrual history. Oligomenorrhea was identified in 5 of 13 of these athletes when they swam approximately 100,000 yards per week. Weight and percentage of body fat were not significantly different between the period of oligomenorrhea and regular menstrual function (P=0.24). Mean and median levels of luteinizing hormone, follicle-stimulating hormone, prolactin, and 17β-estradiol were decreased and catechol estrogens and β-endorphins were increased in serum during the strenuous, when compared with the moderate, training period. The serum levels of the steroid and protein hormones were similar to those of normal cycling, nonexercising control subjects during moderate exercise (60,000 yards per week). The significant differences between β-endorphins and catechol estrogens during periods of strenuous exercise suggest an explanation for oligomenorrhea in female athletes. These hormonal changes result in hypothalamic anovulation, which appears to be reversible, because the hormone levels and menstrual cycles return to normal when the exercise is reduced.